(untitled) (Research, Society and Development, 2021)
The present work sought to propose solutions to the bottlenecks identified in a production process using the quality tool, flowchart in conjunction with the activities carried out by Production Planning and Control-PCP, taking as a premise its great importance within organizations. The case study was carried out in a small company specialized in the manufacture of upholstery, located in the municipality of Codó-MA. By mapping the production process and interviewing the area manager, it was possible to understand the systematic of operations, as well as the main anomalies related to the production process. Material Resource Planning - MRP was defined as the most viable solution to minimize the problems encountered. From research it became possible to recognize that the effective application of the flowchart tool in the PCP is capable of bringing important gains of opportunity for the company, providing benefits, especially in the improvement of the productive process for the resolution of problems and its good flow, giving it a competitive advantage over the competition.